Exogenously Led and Policy-Supported New Path Development in Peripheral Regions: Analytical and Synthetic Routes. (20th October 2017) - Isaksen, Arne; Trippl, Michaela
Abstract: The aim of this article is to explore how new industrial paths emerge and grow in peripheral regional economies. Current conceptualizations of regional path development are based on experiences from core regions and fail to provide satisfactory theoretical explanations of new path-creating activities in peripheral areas. Our conceptual approach combines the notions of path development and knowledge bases, enabling us to distinguish between an analytic and a synthetic route of path creation. We argue that due emphasis should be given to exogenous sources of new path development and policy actions in order to understand how analytical and synthetic routes unfold in peripheral regions. These factors are still underappreciated in prevailing models of path creation. The article contains an analysis of the emergence and evolution of new industries in two peripheral regions in Norway and Austria: the electronics and software industry in Arendal–Grimstad in southeastern Norway, and the software industry in Mühlviertel in Upper Austria. The two industries have developed differently: through the synthetic route based on the emergence and restructuring of manufacturing firms in Arendal–Grimstad and through the analytical route building on the establishment of research facilities in Mühlviertel. Our analysis suggests that the inflow of new analytical and synthetic knowledge from exogenous sources and various types of policy interventions have been vital in sparking the formation of new industrial paths in both regions. The findings clearly challenge uniform, narrowly conceptualized models of industrial evolution and support recent work that advocates a broader theoretical framework to capture exogenously led and policy-supported path-creation processes.